The mystery of the hidden painting - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (New York : Scholastic, 1992)
The Alden children hunt for their late grandmother's necklace that has been missing for years.
Keywords: Orphans -- Fiction; Brothers and sisters -- Fiction; Mystery and detective stories